Wages Differentials and Interregional Migration in the U. S.: An Empirical Test of the "Option Value of Waiting" Theory - Roberto Basile; Jaewon Lim (European Regional Science Association (ERSA), 2006)
The "option value of waiting" theory applied to interregional migration predicts that a potential migrant actually moves only when the wage differential between origin and destination places exceeds a certain threshold, which might be much higher than the Marshallian trigger. In this paper we exploit the panel structure of a dataset on interregional migration among nineteen MSAs in the US from 1993 to 2001 to estimate a modified dynamic gravity model of migration. In particular, using both semi-parametric and GMM estimators (taking into account possible endogeneity of the explanatory variables), we find robust evidence of a non-linear relation between migration and wage differentials. With a wage differential smaller than a certain threshold, people rarely move controlling for the other socioeconomic variables. Only beyond the threshold, the interregional migration grows rapidly proving an important role of the option value of waiting in migration decision process.
Keywords: 330